ANALYSIS OF POST PROCESSING TECHNIQUE CT RENAL ANGIOGRAPHY FOR IDENTIFICATION OF VARIATIONS OF RENAL ARTERIES IN KIDNEY DONOR PREPARATION: LITERATURE REVIEW - Lailatul Muqmiroh; Shesha Rahma Anastasya; Amillia Kartika Sari; Anggraini Dwi Sensusiati; Pramono Pramono (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Visualization of renal artery variations is a prerequisite for kidney donors. Polar variations and number of renal arteries were identified using several prost processing techniques Renal CT Angiography. Objective : To identify variations in the number and polarity of the renal arteries using MPR, MIP, CPR and 3D VR based on a literature review. Analysis with a literature review approach was carried out using secondary data sources from 2012-2022 scientific publication journal articles by comparing the number and polarity of the renal arteries from the MPR, MIP, CPR and 3D VR post-processing techniques on CT renal angiography. MIP and 3D VR are the optimal combination of post-processing techniques for identification of the number and polarity of the renal arteries. The combination of MIP and 3D VR post processing techniques is the optimal post processing technique in depicting the number and polar variations of the renal arteries